Expectant management of adnexal masses in selected premenopausal women: a prospective observational study. (7th April 2013) - Alcázar, J. L.; Olartecoechea, B.; Guerriero, S.; Jurado, M.
ABSTRACT Objective To evaluate the results of expectant management of ovarian cysts with benign ultrasound morphology in selected asymptomatic premenopausal women. Methods This was a prospective cohort study of premenopausal women diagnosed with a persistent adnexal cyst. Patients were selected according to symptoms (asymptomatic), the cyst's appearance on ultrasound (benign) and size (< 8 cm). Patients underwent a follow‐up protocol with transvaginal ultrasound examination at 6‐monthly intervals for 2 years and then annually for at least 3 years. Results The study comprised 166 women (mean age, 40 years) with 192 masses present at inclusion. Twenty‐two women (with 29 masses) were lost to follow‐up. Seventy‐four masses (38.5%) resolved spontaneously (median time from diagnosis to resolution, 40 months). Forty‐nine masses (25.5%) persisted without change (median follow‐up time, 88 (range, 36–192) months). Forty masses (20.8%) were surgically removed; 12 because of increase in size, four because a second lesion appeared during follow‐up, three because of change in appearance and increase in size, five because of surgery for uterine benign or malignant disease, two because of change in appearance without increase in size, one because of clinical suspicion of ovarian torsion and 13 because of the patient's decision in spite of there being no change in the mass. Histology was benign in all but two cases (Stage Ia mucinous ovarian carcinoma and Stage Ia mucinous borderline tumor). During follow‐up 40 new masses in 31 women were diagnosed, of which 21 resolved spontaneously, five (all with benign histology) were surgically removed and 14 were still present at the time of writing. Conclusions Expectant management of cysts with benign ultrasound morphology is a management option in selected asymptomatic premenopausal women. Copyright © 2012 ISUOG. Published by John Wiley & Sons Ltd.